Fertilization strategy and application model using a centrifugal variable-rate fertilizer spreader - Shi, Yinyan; Hu, Zhichao; Wang, Xiaochan; Odhiambo, Morice O.; Sun, Guoxiang (International Journal of Agricultural and Biological Engineering, 2018)
With the sustainable development of precision agriculture and the steady progress of variable-rate fertilization technology, the centrifugal variable-rate fertilizer spreader has attracted research attention due to its lower incidence of crush damage, high efficiency, and low cost. To improve fertilization accuracy and uniformity, spreading performance tests were conducted using this spreader in accordance with the test methods specified in ISO 5690 and ASAE S341.2, in which particle mass was weighed in a two-dimensional matrix of collection boxes. The effects of fertilization strategies that control the feed gate flow rate and the disc rotation speed on particle distribution, and application rate per unit area and effective swath width, were investigated. A variable-rate fertilization model was developed by analyzing the variation characteristics resulting from an increasing and decreasing application rate, and field experiments were conducted to verify its accuracy. The results indicated that when the feed gate flow rate was 300 g/s, the mean application rate was 26.47 g, the standard deviation is 2.81, and the coefficient of variation of particle distribution is at its minimum value of 14.25%. When the disc rotation speed was 600 r/min, the fertilizer was most evenly distributed with a coefficient of variation of 13.86%, and an average effective spreader swath width of 24.51 m. The proposed variable-rate fertilization model showed a high fitting degree with an S-shaped function curve for both increasing and decreasing distribution rates and the yielding coefficients of determination were more than 0.82 and 0.71, respectively. The average error between the model predictions and the test results was 9.47%, and the coefficients of determination for the increasing and decreasing distribution rates were 0.91 and 0.82, respectively, which confirmed the accuracy of the proposed variable-rate fertilization model. This investigation provided a theoretical basis for traditional empirical fertilization using centrifugal variable-rate fertilizer spreaders, and guides the selection of a multiple trajectory, variable-rate fertilization strategy. Keywords: variable-rate fertilization, centrifugal spreader, fertilization strategy, application model DOI: 10.25165/j.ijabe.20181106.3789 Citation: Shi Y Y, Hu Z Z, Wang X C, Odhiambo M O, Sun G X. Fertilization strategy and application model using a centrifugal variable-rate fertilizer spreader. Int J Agric & Biol Eng, 2018; 11(6): 41–48.